1,3-Dipolar cycloaddition reaction of D-glucose-derived nitrone with allyl alcohol: synthesis of 2-hydroxy-1-deoxycastanospermine analogues - Karanjule, Narayan S.; Markad, Shankar D.; Sharma, T.; Sabharwal, Sushma G.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2005)
The synthesis and evaluation of glycosidase inhibitory activity of polyhydroxylated indolizidine alkaloids namely 2-hydroxy-1-deoxycastanospermine 3a,b and 2-hydroxy-1-deoxy-8a-epi-castanospermine 3c,d is reported. The key step involves the intermolecular 1,3-dipolar cycloaddition of allyl alcohol to D-glucose-derived nitrone 4, followed by tosylation, that afforded four diastereomeric sugar-substituted isoxazolidines 5a-d with the desired regioselectivity. The one-pot conversion of 5a-d to pyrrolidines 8a-d by hydrogenolysis, removal of 1,2-acetonoide functionality, and hydrogenation afforded corresponding target molecules 3a-d.

Aziridine carboxylate from D-glucose: synthesis of polyhydroxylated piperidine, pyrrolidine alkaloids and study of their glycosidase inhibition - Dhavale, Dilip D.; Kumar, K. S. A.; Chaudhari, Vinod D.; Sharma, T.; Sabharwal, Sushma G.; PrakashaReddy, J. (Organic & Biomolecular Chemistry, 2005)
The D-glucose derived aziridine carboxylate 5 was obtained from (E)-ethyl-6-bromo-1,2-O-isopropylidene-3-O-benzyl-5-deoxy-alpha-D-xylo-5 -eno-heptofuranuronate 4 through conjugate addition of benzylamine and in situ intramolecular nucleophilic expulsion of bromine. The regioselective aziridine ring-opening, using water as a nucleophile, resulted in the alpha-hydroxy-beta-aminoester 6, which was exploited in the synthesis of six and five membered azasugars 1b/1c and 2b/2c, respectively The glycosidase inhibitory activity of the title compounds was evaluated.